Entre espaços e indivíduos: arquitetura hostil sob a perspectiva conceitual da luta por reconhecimento de Axel Honneth - Santos, Beatriz Leite dos (2024)
This study explores the intersection between hostile architecture, Axel Honneth's theories of Recognition and Reification, and the concepts of Smart and Sustainable Cities, with the purpose of examining their impact on social dynamics and social inclusion in urban contexts. To this end, the research aims to answer: how does the presence of hostile spaces impede or hinder the equal recognition of citizens, affecting the conception of Smart Cities? Adopting a qualitative methodology, based on a descriptive bibliographic study and a hypothetical-deductive approach, the analysis also benefits from visual evidence of hostile architectural elements obtained via Google Street View screenshots, offering examples of hostile elements in the municipality of São Paulo, dated in the tool as captured between the years 2016 to 2023. The dissertation's structure is organized into chapters where the theoretical bases of the concepts of Recognition and Reification are established, followed by the various forms of hostile architecture manifestation and the integration of the concepts of Smart and Sustainable Cities, in consonance with the Sustainable Development Goal (SDG) 11 of the 2030 Agenda, promoting contributions that encompass the issues of hostile architecture with the promotion of inclusive urbanization from Honneth's perspective. In the concluding chapters, the dissertation synthesizes the observations made, offering a critical analysis of the themes. It is believed that this study will significantly contribute to the academic debate regarding the role of social participation, architecture, and urban planning in shaping urban social dynamics, emphasizing the importance of more inclusive and recognized urbanization practices.